AB0700 Evaluation of Primary Biliary Cirrhosis and Anti-Mitochondrial Autoantibodies in Patients with Systemic Sclerosis. (9th June 2015) - Sargin, G.; Senturk, T.; Borazan, S.; Coskun, A.
Abstract : Background: Systemic sclerosis (SSc) associated with primary biliary cirrhosis (PBC) is called Reynold's syndrome. The mechanism between these orders is not clearly understood. Anti-mitochondrial antibody (AMA) for PBC may be detected in 25% of SSc patients (1). Objectives: To analyze PBC and AMA in patients with SSc. Methods: In the period between April 2012 and January 2015, forty-two patients who admitted to our rheumatology clinic with the diagnosis of SSc according to the criteria of "EULAR/ACR" were enrolled. Clinical and demographic datas were obtained retrospectively, Age, sex, hematological, biochemical and autoimmune serology such as anti-nuclear, anti-mitochondrial, anti-Scl-70 and centromere antibodies were evaluated. Primary biliary cirrhosis was diagnosed with abnormal liver and cholestatic parameters, AMA and confirmed by liver biopsy. Mann-Whitney U and chi-square tests were performed as statistical analysis. Results: Seven patients with the limited SSc were female. (Female/Male: 3, 5). The ratio for diffuse SSC was 1, 2. Mean age for diffuse SSc was 46, 3±9, 6 years. Limited SS was found in 9 patients (21, 4%), while the remaining patients (n=33) had diffuse SS. Esophageal, cardiac, and lung involvement was found in 13, 21, and 23 patients, respectively. AMA, anti-Scl-70, and anti-centromere antibodies were detected in 7, 1%, 28, 3% and %43, 7% patients with diffuse SSc. All of PBC had also diffuse SSc disease. There was elevated hepatic parameters such alkaline phosphatase, gamma-glutamyl transpeptidase, and hepatomegaly proven by ultrasonography in all patients with PBC. Also, there were strongly association between AMA and anti- centromere antibodies in patients with diffuse SSc (p=0, 001). We found calcinosis less frequently in Reynold's syndrome. Conclusions: Autoimmune diseases may be associated with other autoimmune diseases. The combination of SSc and PBC is rare. However, the rheumatologist should kept in mind Reynold's syndrome for early diagnosis and therapy. References: Chou MJ, et al. Reactivity of anti-mitochondrial antibodies in primary biliary cirrhosis and systemic sclerosis. J Formos Med Assoc 1992;91:1075-80. Disclosure of Interest: None declared